INTER-SPECIFIC COMPETITION AND FISHING EFFECT TO POPULATION DYNAMIC OF BALI SARDINE (SARDINELLA LEMURU) - Andhika Prima Prasetyo; Rudy Masuswo Purwoko (Research Center for Fisheries, 2016)
Stock-recruitment relationship of Bali sardine was investigated based on Beverton-Holt model by assuming inter-specific competition. Model is modified to incorporate the effect of fishing pressure that is density-independent to population dynamic by developing scenario fishing on adult and/or juvenile population. The results show that harvested adult the dramatic decline of recruitment supply. However, harvested juvenile is led to the positive response to population size, as an increase in fishing mortality rate will reduce competition mortality rate. Precautionary approach required by considering bipartite life cycle.